Exploring the Promotive Effects and Mechanisms of Different Polyphenolic Extracts from Prinsepia utilis Royle Seed Shell on Tyrosinase - Shuang Ma; Xiuqing Zheng; Yuanyue Zhang; Shuai Zhao; Junjie Yi; Shengbao Cai (Foods, 2022)
Prinsepia utilis Royle (P. utilis) is commonly used as a food ingredient and herbal medicine according to folk records, yet little research has been done on the seed shell, a processing waste. The aim of this study was to investigate the distribution of polyphenolic components and the tyrosinase activation activity of different extracts from the seed shell by UHPLC-ESI-HRMS/MS, in vitro tyrosinase activity assay, molecular docking and molecular dynamics. A total of 16 phytochemicals were identified, of which (+)-catechin and (−)-epicatechin were the major polyphenolic compounds. Both the esterified and insoluble bound polyphenols exhibited tyrosinase activation activity, and the esterified polyphenols showed better tyrosinase activation activity. (+)-Catechin and (−)-epicatechin might be the main activators of tyrosinase, both of which may act as substrate to affect tyrosinase activity. By molecular docking and molecular dynamics simulation studies, (+)-catechin and (−)-epicatechin can be efficiently and stably bound to the tyrosinase active site through hydrogen bonds, van der Waals forces and π-bonds. The results of this study may not only provide a scientific basis for exploring P. utilis seed shell as a potential activator of tyrosinase, but also contribute to the high value utilization of P. utilis processing by-products.